Pengaruh Pelatihan Dan Beban Kerja Terhadap Kinerja Karyawan PT. XYZ - Anah Indriyanah; Dian Sudiantini; Bintang Narpati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out whether there is an influence Training and Workload on Employee Performance at PT. XYZ. The method used in this research is a quantitative method. The population and sample in this research amounted to 110 employees. The sample collection technique uses saturated sampling where the entire population is used for the sample. The data collection technique is by distributing questionnaires and processing using the SPSS version 29 application. Research This study uses multiple linear regression analysis and hypothesis testing using the t test and f test. The results of this research show that in the partial test (t test) the training variable has a partial effect on employee performance at PT. XYZ with a calculated t value of 2.488 > t table 1.982 with a sig value. 0.014 < 0.05, the workload variable has a partial effect on employee performance at PT. XYZ with a calculated t value of 5.476 > t table 1.982 with sign. 0.001 < 0.05, and the results of the simultaneous test (f test) of the training and workload variables simultaneously influence employee performance at PT. XYZ with a calculated F value of 45.360 > F table 3.08 and a sig. 0.001 < 0.05.